2018
DOI: 10.1038/s41556-018-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis identifies a CD33+ subset of human cord blood cells with high regenerative potential

Abstract: Elucidation of the identity and diversity of mechanisms that sustain long-term human blood cell production remains an important challenge. Previous studies indicate that, in adult mice, this property is vested in cells identified uniquely by their ability to clonally regenerate detectable, albeit highly variable levels and types, of mature blood cells in serially transplanted recipients. From a multi-parameter analysis of the molecular features of very primitive human cord blood cells that display long-term ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 44 publications
7
34
1
Order By: Relevance
“…Unlike recent studies on human HSC populations 2 , 49 , 50 , we administered human EPO to NSG mice to overcome the limitation in erythroid differentiation seen in this xenograft model 51 . We demonstrate that extending the range of lineage read-out to Ery differentiation significantly expands our understanding of heterogeneity within the phenotypic HSC/MPP pool, and identify rare multipotent (Ery/My/Ly) long-term repopulating HSC within the CLEC9A hi CD34 lo fraction of the HSC/MPP and 49f + HSC pools (Subset1).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike recent studies on human HSC populations 2 , 49 , 50 , we administered human EPO to NSG mice to overcome the limitation in erythroid differentiation seen in this xenograft model 51 . We demonstrate that extending the range of lineage read-out to Ery differentiation significantly expands our understanding of heterogeneity within the phenotypic HSC/MPP pool, and identify rare multipotent (Ery/My/Ly) long-term repopulating HSC within the CLEC9A hi CD34 lo fraction of the HSC/MPP and 49f + HSC pools (Subset1).…”
Section: Discussionmentioning
confidence: 99%
“…22 Barcoding analyses of human CD34 1 HSPCs engrafted in nonobese diabetic-severe combined immunodeficiency gammaC 2/2 mice also suggest that the HSPC potential is heterogeneous in humans. 23,24 However, the long-term repopulation capacity is limited by the animal's life span, and the interpretation of these data in mice is complicated by a skewing of human cell differentiation toward lymphoid lineages.…”
Section: Introductionmentioning
confidence: 99%
“…These cells also possessed molecular characteristics consistent with being more deeply quiescent. Thus, these and other studies again point to the heterogeneity of human HSCs and the need for more defined biomarker identification of the most primitive HSCs …”
Section: Discussionmentioning
confidence: 82%
“…Although we have used hCD33 as a marker of the myeloid lineage after transplant, recent studies have identified this biomarker on a subset of human UCB hCD34 + CD38‐CD45RA‐CD90 + CD49f + HSCs, particularly on those that contain all the serial regenerative HSC activity in human UCB. These cells also possessed molecular characteristics consistent with being more deeply quiescent.…”
Section: Discussionmentioning
confidence: 99%